1992
DOI: 10.1172/jci115787
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in left ventricular diastolic function in conscious dogs with pacing-induced heart failure.

Abstract: We investigated in conscious dogs (a) the effects of heart failure induced by chronic rapid ventricular pacing on the sequence of development of left ventricular (LV) diastolic versus systolic dysfunction and (b) whether the changes were load dependent or secondary to alterations in structure. LV systolic and diastolic dysfunction were evident within 24 h after initiation of pacing and occurred in parallel over 3 wk. LV systolic function was reduced at 3 wk, i.e., peak LV dP/dt fell by -1,327±105 mmHg/s and ej… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(67 citation statements)
references
References 57 publications
5
60
2
Order By: Relevance
“…18 Thus, one mechanism by which BK exerts its protective effect on myocardial contractile function may be related to its effects on LV diastolic function. In agreement with previous reports, 15,16 this study showed a rightward shift of LV diastolic pressure-diameter curve, with an unchanged LV chamber stiffness after 3 weeks of pacing in vehicle-treated dogs. Chronic BK treatment reduced the rightward shift of the LV diastolic pressure-diameter relation but did not change LV chamber stiffness, which is in agreement with a recently developed concept.…”
Section: Tonduangu Et Al Chronic Effects Of Bradykinin In Heart Failuresupporting
confidence: 93%
See 1 more Smart Citation
“…18 Thus, one mechanism by which BK exerts its protective effect on myocardial contractile function may be related to its effects on LV diastolic function. In agreement with previous reports, 15,16 this study showed a rightward shift of LV diastolic pressure-diameter curve, with an unchanged LV chamber stiffness after 3 weeks of pacing in vehicle-treated dogs. Chronic BK treatment reduced the rightward shift of the LV diastolic pressure-diameter relation but did not change LV chamber stiffness, which is in agreement with a recently developed concept.…”
Section: Tonduangu Et Al Chronic Effects Of Bradykinin In Heart Failuresupporting
confidence: 93%
“…As previously described, 3,14,15 in 16 beagle dogs weighing 13 to 21 kg anesthetized with 1 vol% halothane, a left thoracotomy was performed under sterile conditions for implantation of Tygon catheters in the descending aorta and left and right atria, a micromanometer in the left ventricular (LV) cavity, 2 pacing leads on the right ventricle, an ultrasonic flow probe around the root of aorta, and piezoelectric crystals in the LV to measure the internal short-axis and wall thickness in the same equatorial plane. The maintenance of animals, including postoperative care, analgesia, and antiinfectious prophylaxis, were kept in accordance with the Guide for the Care and Use of Laboratory Animals (NIH Publication No.…”
Section: Instrumentationmentioning
confidence: 99%
“…The presence of atrial fibrillation can potentially cause an adverse effect in several different ways (54)(55)(56)(57). Loss of atrial enhancement of ventricular filling may compromise cardiac output.…”
Section: Recommendationsmentioning
confidence: 99%
“…Irregular contractions and rapid fastening heart beats cause decrease in left ventricular contractility and filling and impaired relaxation (19)(20)(21)(22). Intrinsic contractility of left atrium plays a major role in left ventricular diastolic filling (23).…”
Section: Discussionmentioning
confidence: 99%